2016
DOI: 10.1007/s00330-016-4628-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of sub-centimetre breast lesions: combining BI-RADS-US with strain elastography and contrast-enhanced ultrasound—a preliminary study in China

Abstract: • Evaluating breast lesions with SE and CEUS could increase the diagnostic specificity • SE and CEUS offer alternatives to biopsy and possibly allow shorter-interval follow-ups • BI-RADS-US combined with CEUS exhibited the best diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…To evaluate differences related to the ethnicity of patients enrolled in the study and variation related to ultrasonography itself, we determined the cutoff value for ultrasound-based BI-RADS scores and PD-1 mRNA expression using ROC curves. The sensitivity and specificity for BI-RADS scores were 0.752 and 0.909, respectively, and AUC was 0.906 (0.860–0.952), with a cutoff value for BI-RADS 4C, which is consistent with previous studies 8,49…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To evaluate differences related to the ethnicity of patients enrolled in the study and variation related to ultrasonography itself, we determined the cutoff value for ultrasound-based BI-RADS scores and PD-1 mRNA expression using ROC curves. The sensitivity and specificity for BI-RADS scores were 0.752 and 0.909, respectively, and AUC was 0.906 (0.860–0.952), with a cutoff value for BI-RADS 4C, which is consistent with previous studies 8,49…”
Section: Discussionsupporting
confidence: 90%
“…Breast ultrasound is a routine and valuable measure to differentiate malignant and benign breast tumors 8,47. Jeffers et al4 predicted breast cancer risks by BI-RADS classification, with an AUC of 0.68.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in keeping with the recent study of Park et al investigating shear wave elastography of breast non‐mass lesions, showing that smaller lesion size of malignant lesions are associated with false negative results . The addition of contrast‐enhanced US, in combination with strain elastography is a promising technique which has been shown to improve diagnostic performances in case of small breast lesions . With respect to tumor histologic features, malignant lesions that are soft, such as DCIS, necrotic tumors and mucinous carcinoma can be misclassified as benign.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, a relationship has been found between the elasticity imaging/B-mode ratio on SE and tumor grades in breast cancer [22]. A recent preliminary study has indicated that Contrast Enhanced Ultrasound (CEUS) provides superior diagnostic performance in sub-centimetre breast lesions, offering promising alternatives to biopsy [33]. Given these updates in the field of sonoelastography, we set out to explore the relationship between lesion size and the influence of SE on ILC classification, in order to identify an optimal size threshold at which SE adds significantly more value to the examination.…”
Section: Discussionmentioning
confidence: 99%